EXPLORING LANGUAGE AS THE TOOL FOR RELIGIOUS LEADERS IN COUNTERING RADICALISATION AND RELIGIOUS EXTREMISM AMONG THE YOUTH IN EASTLEIGH, NAIROBI COUNTY - SHONHAYI, GIVEMORE (Advances in Social Sciences Research Journal, 2019)
The gist of this study was to explore language as a tool for religious leaders in preventing and countering radicalisation and religious extremism among the youth. This study emphasised on language an indispensable tool that religious leaders can use in curbing this recruitment which has claimed lives and has had economic repercussions. The study specifically assessed the collaboration between the Government of Kenya (GoK) and religious leaders in Eastleigh towards countering radicalisation and religious extremism among the youth and it proposes a common discourse that religious leaders could use in preventing radicalisation and religious extremism of the youth. The study was anchored by the Social Movement Theory (SMT). The target population comprised of the religious leaders, security operatives and youths in Eastleigh. The study implored simple random sampling technique. In total a sample of 100 respondents were randomly selected from the study site. The researchers collected primary data from the respondents by administering questionnaires (to the youth) and interview schedules on religious leaders and the security personnel. The data was analysed using quantitative and qualitative techniques. Quantitative data was analysed using Statistical Package for Social Sciences (SPSS) version 23 program while qualitative was analysed through narrative descriptions. The study findings established that among many other tools and means, language is key in curbing youth radicalisation and religious extremism. It also revealed that the Government of Kenya should directly engage the religious leaders on matters prevention of youth radicalization and religious extremism. The youth bemoaned lack of employment and political participation as the factors that pull them to radicalisation and religious extremism. They also want to be fully engaged in occasions where language is used between the GoK and Religious leaders.